Optimising mobile text input by virtual keyboards using visual clues. - Lee, Hong Ee. (2008)
The main objective of this dissertation was to investigate the use of visual clues on mobile text entry. Based on ISO 92411-11 on the measure of system usability, an application should be tested on its effectiveness and satisfaction. For system effectiveness, a mobile application was developed for conducting usability tests and tabulate the text entry speed and accuracy. In addition, percevied effectiveness, ease of learning virtual keyboards and usefulness of visual clues were also captured.